Open Abdomen is the Equal of Catastrophic or Hostile? - Ricardo, Lupio García Baruj; Itzel, López García Evelyn; Mariana, González Valiente; Gema, Méndez Barrón; Rogelio, Ortiz Ramírez Mario; de Jesús, Urbina Cabello José; Montserrat, Herrera Medina Jessica; Astrid, Ortiz Vargas; Atzimba, Zepeda Carrillo Carol; Adolfo, García Sánchez Morelos; Antonio, Moreno Ramírez Diego (British Journal of Healthcare and Medical Research, 2024)
Introduction: the aggression that represents a surgical event for whatever reason, entails consequences or sequelae that are sometimes devastating, for the patient and the health system itself. Objective: to describe the experience of open abdomen during 7 years of management, in the health system in Mexico. Method: study with a retrospective, longitudinal, observational, and descriptive design in the Surgery Service, multicenter study of four second and third level health care hospitals. Results: records of a total of 385 patients are reviewed, of which 234 are men (61%) and 151 are women (39%). With an age range from 17 years to 93 years. Patients potentially undergoing open abdomen management were classified into three groups. The overall adjusted mortality was 5 patients, which represents 1.29% of the total study. It culminated in the result of 5 cases with catastrophic abdomen and 3 patients with hostile abdomen. Discussion: the question is, what is the surgical indication for leaving the patient's abdomen open? Abdominal hypertension, abdominal sepsis, and damage control surgery, in trauma surgery, which is why it is specified and classified into open abdomen, catastrophic abdomen and hostile abdomen. Conclusion: Strategies must be taken to avoid at all costs the open abdomen and therefore its complications, considering the surgical findings, the surgeon's expertise, material, and human resources and/or infrastructure.